2014
DOI: 10.1007/s10519-014-9659-5
|View full text |Cite
|
Sign up to set email alerts
|

GE Covariance Through Phenotype to Environment Transmission: An Assessment in Longitudinal Twin Data and Application to Childhood Anxiety

Abstract: We considered identification of phenotype (at occasion t) to environment (at occasion t + 1) transmission in longitudinal model comprising genetic, common and unique environmental simplex models (autoregressions). This type of transmission, which gives rise to genotype-environment covariance, is considered to be important in developmental psychology. Having established identifying constraints, we addressed the issue of statistical power to detect such transmission given a limited set of parameter values. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…As others and we have pointed out elsewhere (Beam et al, de Kort et al, 2014; Dolan et al, 2014), P=>E effects necessarily change the meaning of the nonshared environmental factors. We provided a simple numerical check to evaluate whether P=>E alters the meaning of the nonshared environment by subtracting the model estimated NSE’ correlation matrix generated by the P=>E model from the model estimated NSE correlation matrix generated by the genetic simplex model without P=>E. The differences were near zero, which suggests that the traditional analytical meaning of the NSE seems to be well preserved in the context of P=>E estimation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As others and we have pointed out elsewhere (Beam et al, de Kort et al, 2014; Dolan et al, 2014), P=>E effects necessarily change the meaning of the nonshared environmental factors. We provided a simple numerical check to evaluate whether P=>E alters the meaning of the nonshared environment by subtracting the model estimated NSE’ correlation matrix generated by the P=>E model from the model estimated NSE correlation matrix generated by the genetic simplex model without P=>E. The differences were near zero, which suggests that the traditional analytical meaning of the NSE seems to be well preserved in the context of P=>E estimation.…”
Section: Discussionsupporting
confidence: 63%
“…Others have developed and applied longitudinal P=>E models to child cognitive and psychiatric twin data from the Netherlands Twin Registry to explain how biosocial processes produce behavioral diversification (de Kort et al, 2014; Dolan, de Kort, van Beijsterveldt, Bartels, & Boomsma, 2014). While a study that compares and contrasts each P=>E version would be fruitful for understanding how people select environments and how environments evoke behavior, such a study falls outside the scope of the current report on reviving the LTS.…”
Section: Different P=>e Transmission Modelsmentioning
confidence: 99%
“…Note that the rational to introduce Ph->E transmission in the alternative AE model and not in the ACE model is based on statistical considerations. De Kort et al and Dolan et al studied the issues of parameter identification and power when allowing Ph->E transmission in both the ACE model and the AE* [19,20]. They showed that the resolution of the Ph->E transmission parameters (α t and γ t ) is extremely poor in the presence of an independent C simplex (i.e., Equation (5)).…”
Section: The Ae* Simplex Model With Ph->e Transmission Applied To Twimentioning
confidence: 99%
“…In presence of Ph->E transmission, the correlations between ζ E*1t and ζ E*2t are due to shared environmental influences in addition to the correlated environment originating in the Ph->E transmission [19]. Dolan et al established that, given four time points, the parameters α t and γ t are identified subject to equality constraints (e.g., α 2 = α 3 and γ 2 = γ 3 ) [20]. Here, we impose the over-identifying constraint α t = α t-1 and γ t = γ t-1 , t = 2, 3, 4, and therefore drop the time subscript (i.e., the parameters are denoted α and γ).…”
Section: The Ae* Simplex Model With Ph->e Transmission Applied To Twimentioning
confidence: 99%
“…One could, for example, make a post hoc decision to employ an ADE model, or speculate about epistatic effects that might tend to inflate MZ correlations relative to DZ. Alternatively, some of us (Beam & Turkheimer, 2013) and others (Dolan et al, 2014) have explored a class of models that routinely produce DZ twin correlations that decline rapidly with age and quickly lead to DZ correlations that are less than half the MZ correlation. These models, called reciprocal effects models or P => E (phenotype to environment) models, are used to show how people’s exposure to environments (either randomly or systematically) can trigger a recursive process between individuals and their subsequent environmental exposure.…”
Section: Discussionmentioning
confidence: 99%